Analysis Of Mathematics Student Error To Solve Problems Of Linear Programs - Zulhendri; Ahmad Fauzan; Made Arnawa; Edwin Musdi; Yerizon (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The goal of this research is  to describe the analysis of mathematics students error to solve problem of linear programs. This research belongs to the type of qualitative research with using a descriptive approach.  The data collection technique is done by giving tests in the form of linear program story questions and interviews. This study used in fifth semester of the students of mathematics of Pahlawan University. The results showed that the types of conceptual errors are: a) making graphic error solution, b) error in using the concept of a variable that will be used, c) identify what is asked and d) choosing error symbol. Procedural errors are: a) error in choosing the strategy to be used in problem solving, b) error in apply strategy to solve the problem, and c) error in viewing return what is the solution obtained is in accordance with what known and asked. Causative factor students make mistakes in solving program problems linear:  a) Students are not accustomed to solving story problems so that students have difficulty transform into a mathematical model b) Students do not understand the concept of symbols inequalities c) Students are less proficient at making graphs including determining the area completion d) Students do not understand the concept of extreme points e) Students are less thorough in performing calculation operations